CONSUMER BEHAVIOR AND ARTIFICIAL INTELLIGENCE: THE ROAD TO PERSONALIZED SHOPPING EXPERIENCES - LAZEA RUXANDRA; NICHITA ANCA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The present article delves into how nowadays advancements in artificial intelligence can shape consumer behavior. Due to the novelty degree of this research topic, we choose a theoretical approach by conducting a literature review of relevant studies. We identified the main advantages and disadvantages that artificial intelligence triggers for companies and consumers, which appeared after the emergence of this cutting-edge technology. We also addressed in detail the crucial possibility for companies of personalizing shopping experiences and catering to consumers’ needs with the help of AI tools integrated into next-level search platforms, which can learn clients’ preferences and recommened products/services with a high accuracy degree.